MODERN DIAGNOSTIC AND TREATMENT TECHNIQUES FOR MANDIBULAR AND MAXILLARY INJURIES - FROM RECONSTRUCTION TO INTERNAL FIXATION - Aleksnadra Korżel,; Ewelina Roksana Wojna,; Karolina Górowska,; Gabriela Ragan,; Patrycja Anita Kobrzyńska,; Jędrzej Mogilany,; Julia Niedźwiecka,; Kamil Źródłowski, (International Journal of Innovative Technologies in Social Science, 2026)
Background: Injuries of the mandible and maxilla contribute to a large part of maxillofacial trauma, which often require complex diagnostics and therapeutics. Recent developments in imaging, computer-aided design and manufacturing, biomaterials, and reconstructive methods have significantly affected clinical assessment and surgical outcomes.Methods: This is a review of the evidence from 21 peer-reviewed studies published between 2014 and 2025, sourced through Scopus, PubMed, Web of Science, and publisher databases. Reconstruction, materials science and complication profiles are part of this series.Results: Epidemiological trends and diagnostic jigsaw were uniformly emphasised across studies, in which CT, CBCT and 3D reconstruction were considered fundamental. The accuracy of fracture repositioning and reduction during image-guided or navigated surgery was significantly higher. The digital workflows, together with VSP and CAD/CAM drilling guides, enabled an accurate reconstruction of the mandible with improved functional and cosmetic results. Comparative studies demonstrated the superiority of ORIF over closed reduction for both condylar and mandibular fractures with delayed treatment, with a negative impact on functional outcome. Resorbable implants perform well as an alternative to titanium-level fixation systems, with reduced reoperation requirements and acceptable stability profiles.Conclusion: Modern diagnostic and therapeutic procedures, such as high-resolution imaging, navigation, VSP, CAD/CAM technology, and bioresorbable fixation techniques, significantly enhance precision, reducing complications and promoting optimal functional rehabilitation with maximum facial symmetry in mandibular and maxillofacial trauma. The current evolution of digital workflows and materials is likely to enhance clinical outcomes.